Caracterização da (Des)Informação das Narrativas sobre Vacinação em Grupos Públicos no WhatsApp no Brasil - Santos, Jônatas H. dos; Reis, Julio C. S.; Melo, Philipe de F.; Olivetti, João F. H.; Silva, Thales H.; Guimaraes, Matheus; Souza, Glaucio de; Rodrigues, Marco A. G.; Goncalves, Marcos A.; Benevenuto, Fabricio; Lima, Cristiano X. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the Web, 2025)
WhatsApp has become one of the main channels for disseminating health information in Brazil, especially during the COVID-19 pandemic. In this work, we investigate the spread of (mis)information about vaccines in public groups on the platform, focusing on identifying dominant narratives, engagement patterns, and connections to other online information sources. Using a set of 84,640 messages collected between 2020 and 2023, we applied Natural Language Processing (NLP) techniques, including topic modeling (BERTopic) and textual similarity analysis. Overall, the results show that alarmist, misinformative, and politicized content is prevalent, with many messages repeated across multiple groups. We also observed a concentration of activity among a few highly active users, suggesting coordinated amplification strategies. This analysis helps to understand the mechanisms of misinformation spread in private messaging environments and provides insights for public policy and digital health countermeasures.